Neutrophil-to-lymphocyte ratio is a prognostic factor for colon cancer: a propensity score analysis - Mazaki, Junichi (BMC Cancer, 2020)
BACKGROUND: A large number of patients suffer recurrence after curative resection, and mortality from colon cancer remains high. The role of systemic inflammatory response, as reflected by neutrophil-to-lymphocyte ratio (NLR), in cancer recurrence and death has been increasingly recognized. This study aimed to analyze long-term oncologic outcomes of Stage II-III colon cancer to examine the prognostic value of NLR using a propensity score analysis. METHODS: A total of 375 patients with colon cancer underwent radical surgery between 2000 and 2014 at Tokyo Medical University Hospital. Long-term oncologic outcomes of these patients were evaluated according to NLR values. A cut-off NLR of 3.0 was used based on receiver operating characteristic curve analysis. Primary outcomes were overall survival (OS) and relapse-free survival (RFS). An analysis of outcomes according to tumor sidedness was also performed. RESULTS: Patients with lower NLR values (“lower NLR group”) were more likely to have lymph node metastasis compared to those with higher NLR values (“higher NLR group”) before case matching. After case matching, clinical outcomes were similar between the two groups. There were no significant differences in 5-year OS and 5-year RFS rates between the two groups before case matching based on propensity scores. After case matching, 5-year OS rates were 94.5% in the lower NLR group (n = 135) and 87.0% in the higher NLR group (n = 135), showing a significant difference (p = 0.042). Five-year RFS rates were 87.8% in the lower NLR group and 77.9% in the higher NLR group, also showing a significant difference (p = 0.032). Among patients with left-sided colon cancer in the matched cohort, 5-year OS and 5-year RFS rates were 95.2 and 87.3% in the lower NLR group (n = 88), respectively, and 86.4 and 79.2% in the higher NLR group (n = 71), respectively, showing significant differences (p = 0.014 and p = 0.047, respectively). CONCLUSIONS: The NLR is an important prognostic factor for advanced colon cancer, especially for left-sided colon cancer.